AB0112 CSD-125, A Soft Coral-Derived Anti-Inflammatory Compound, Attenuates Joint Destruction via Osteoclastogenesis in A Type II Collagen-Induced Arthritis Rat Model. (15th July 2016) - Lin, Y.-Y.; Lin, S.-C.; Li, H.-P.; Jean, Y.-H.; Wen, Z.-H.
Abstract : Background: Rheumatoid arthritis (RA) is a common rheumatic disease that is characterized by synovial inflammation of the synovial tissue that lines the joints [1]. Osteoclasts become active and mature by stimulation of inflammatory cytokines such as macrophage colony-stimulating factor (M-CSF), interleukin-1b (IL-1b), interleukin-17A (IL-17A), and tumor necrosis factor-a (TNF-a), and also play a critical role in the bone destruction in RA [2]. Soft corals have been considered an important resource of anti-inflammatory agents that may be beneficial for treating inflammatory diseases [3–5]. Objectives: In this present study, we investigated the therapeutic effects of CSD-125, a soft coral-derived compound in type II collagen-induced arthritis (CIA), via its role in the anti-osteoclastic pathway. Methods: A rat model of CIA was established, and knee joint tissue destruction was evaluated in rats treated with and without CSD-125 by the RA index, histopathology, immunohistochemistry, and western blotting. We also analyzed the level of pro-inflammatory cytokines such as M-CSF and IL-17A in the blood serum. Results: The results demonstrated that CSD-125 significantly attenuated CIA-induced RA progression in rats. CSD-125 also decreased the expression of osteoclast-related proteins, including cathepsin K, matrix metalloproteinases-9, matrix metalloproteinases-2, cluster of differentiation molecule 11B, nuclear factor of activated T cells, cytoplasmic 1 (NFATC 1), and triggering receptor on myeloid cells 2 (TREM 2), in multinucleated cells. Moreover, CSD-125 reduced the number of cells showing positive expression of IL-17A, IL-1b, and TNF-a, phospho-extracellular signal-regulated kinases (p-ERK), phospho-c-Jun N-terminal kinase (p-JNK), and phospho-p38 (p-P38) in the synovial tissue of CIA-rats. The levels of M-CSF and IL-17A also decreased following administration of CSD-125 to CIA-rats. Conclusions: These results provide strong support that CSD-125 could attenuate the joint destruction in type II CIA, likely through inhibition of osteoclast activation. References: Koenders, M.I. and W.B. van den Berg, Novel therapeutic targets in rheumatoid arthritis. Trends Pharmacol Sci, 2015. Shiozawa, S., et al., Pathogenesis of joint destruction in rheumatoid arthritis. Arch Immunol Ther Exp (Warsz), 2011. 59(2): p. 89–95. Blunt, J.W., et al., Marine natural products. Nat Prod Rep, 2015. 32(2): p. 116–211. Lin, Y.Y., et al., A soft coral-derived compound, 11-epi-sinulariolide acetate suppresses inflammatory response and bone destruction in adjuvant-induced arthritis. PLoS One, 2013. 8(5): p. e62926. Gonzalez, Y., et al., Marine Diterpenoids as Potential Anti-Inflammatory Agents. Mediators Inflamm, 2015. 2015: p. 263543. Acknowledgement: This study was supported by grants from the Ministry of Science and Technology (MOST 103–2628-B-110–002-MY3 and MOST 104–2325-B-110–001) of Taiwan and Pingtung Christian Hospital, Taiwan. Disclosure of Interest: None declared